A Machine Learning Approach To Evaluate The Security Of Ultra-lightweight Block Ciphers - Lee, Ting Rong (2021)
Traditional cryptanalysis is typically performed using manual calculations or search- ing algorithms,which can be computationally costly and cannot produce additionalin- sights apart from what has been dictated by the cryptanalyst.